Low-temperature heat capacity of fullerite C60 doped with nitrogen - Gurevich, A.M.; Terekhov, A.V.; Kondrashev, D.S.; Dolbin, A.V.; Cassidy, D.; Gadd, G.E.; Moricca, S.; Sundqvist, B. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
The heat capacity Cm of polycrystalline fullerite C60 doped with nitrogen has been measured in the temperature interval 2-13 K. The contributions to the heat capacity from translational lattice vibrations (Debye contribution), orientational vibrations of the C60 molecules (Einstein contribution), and from the motion of the N2 molecules in the octahedral cavities of the C60 lattice have been estimated. However, we could not find (beyond the experimental error limits) any indications of the first-order phase transformation that had been detected earlier in the dilatometric investigation of the orientational N2-C60 glass. A possible explanation of this fact is proposed.